Programmed labour compared with expectant management: is it truly a need of new millennium? - Shinde, Madhukar J.; Sabale, Umesh S.; Mehendale, Savita S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The mechanism triggering the initiation of human parturition is still an enigma. At term a series of complex physiological, biochemical and physical processes cascade resulting in delivery of the fetus. This study deals exclusively with comparison of normal labour, induction of labour with prostaglandin, and with augmentation by intracervical insertion of PGE2 tablets, amniotomy and smooth muscle relaxant. Advantages and disadvantages of each of the above methods are compared with expectant management of labour. Aim of this study was to compare pros and cons of programmed labour that to with expectant management. Methods: Study was conducted in Department of Obstetrics and Gynaecology, Bharati Hospital and Research Centre, Pune. It was a prospective randomized clinical trial. 100 pregnant full term women, were selected for each group. At 0 hour primiprost tablet is inserted into the vagina close to the cervix. Frequency of repetition of tablet will be at three hours interval. Patient will be monitored. Results: The youngest one being of age 17 years and the eldest being of age 29 years. In this, we observed those primi and 2nd gravida patients 2-2 tablets each in latent phase and 1-1 tablets in active phase. The induction delivery Interval in primigravida was observed to be of average of 9 hours. While in II Gravida was 6.5 hours, in III Gravida 5.5 hours and in IV Gravida 4 hours. Conclusions: It has been proved beyond doubt that by programmed labour, the patient definitely can get the benefit of decrease in duration of labour.